Frequency Response Analysis in Optical Rotation Detection System of SERF Magnetometer - BOZHENG XING; JIXI LU; CHANG SUN; TINGTING YU; YUE WU; YANAN GAO; BANGCHENG HAN (Physical Science: New Insights and Developments Vol. 1, 2025)
Optical rotation detection systems are widely used in various kinds of atomic sensors, such as atomic magnetometers, co-magnetometers, and nuclear magnetic resonance (NMR) gyroscopes; and appear in many applications such as fundamental physics, biomagnetism, magnetism test, etc. The study analyses the frequency responses to three-axis dynamic magnetic fields in optical rotation detection systems (ORDS) of Spin-Exchange Relaxation-Free (SERF) magnetometers. Because of the imperfections of the optical elements, the probe light is actually elliptically polarised in ORDS, which can polarise the atom ensemble and cause the responses to the three-axis magnetic field. Theoretically it analyse the frequency responses to the sinusoidal magnetic field, and prove that the responses are closely associated with the DC magnetic field. The values of the DC magnetic fields are calculated with special frequency points, called ‘break points’, in the transverse responses. The relationships between the DC magnetic field and the sensitivities of ORDS, and effectively suppress the magnetic noise responses with the residual magnetic field compensation. The paper demonstrated the influence of elliptically polarised light on the sensitivity of ORDS in SERF magnetometers. The elliptically polarised probe light polarises the alkali atom ensemble, which leads to the responses of the magnetic noise in the shield. Finally, the sensitivity of ORDS is improved by approximately two times at 10-20 Hz. This method is beneficial for improving probe sensitivity in SERF magnetometers, co-magnetometers, and NMR gyroscopes.